2016
DOI: 10.1088/1751-8113/49/14/145004
|View full text |Cite
|
Sign up to set email alerts
|

Joint probability distributions for projection probabilities of random orthonormal states

Abstract: Abstract. A finite dimensional quantum system for which the quantum chaos conjecture applies has eigenstates, which show the same statistical properties than the column vectors of random orthogonal or unitary matrices. Here, we consider the different probabilities for obtaining a specific outcome in a projective measurement, provided the system is in one of its eigenstates. We then give analytic expressions for the joint probability density for these probabilities, with respect to the ensemble of random matric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For general unitary transformations from SU (N ) we showed that the overlap distribution can be computed, in principle, following a method introduced in Ref. [14]. The solution is based on the calculation of the joint probability distribution (JPD) of partial overlaps, for which we could obtain a surprisingly simple analytical expression in the qutrit, i.e., SU (3), case.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For general unitary transformations from SU (N ) we showed that the overlap distribution can be computed, in principle, following a method introduced in Ref. [14]. The solution is based on the calculation of the joint probability distribution (JPD) of partial overlaps, for which we could obtain a surprisingly simple analytical expression in the qutrit, i.e., SU (3), case.…”
Section: Discussionmentioning
confidence: 99%
“…We will closely follow the derivation for the unitary case in Ref. [14]. According to this work, Eq.…”
Section: Jpd For General Casementioning
confidence: 97%
See 3 more Smart Citations